2020
DOI: 10.1111/jpn.13457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy on antioxidant capacity, glucose–lipid metabolism and meat fatty acid profile of Holstein bulls at different ages

Abstract: This experiment was conducted to investigate the effects of dietary energy on antioxidant capacity, liver glucose–lipid‐related gene expressions and meat fatty acid of Holstein bulls. Thirty‐six Holstein bulls (age, 17.0 ± 0.49 months; body weight, 493.3 ± 39.7 kg) were randomly allocated to three dietary treatments. The metabolizable energy of diets was 10.12, 10.90 and 11.68 MJ/kg. Bulls in each dietary treatment were sampled at the age of 20, 23 or 26 months. Results showed that serum glutathione peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Therefore, it makes no sense to consider the sum of these three fatty acids, as it is usually done to limit beef in the diet. Wang et al (2021) found that the increase in age decreased the contents of C15:0, C18:0, and the sum of SFA and increased the proportions of C14:1 and C16:1. Regarding these fatty acids in our study, only C18:0 showed an increase in its content with increasing slaughter age.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it makes no sense to consider the sum of these three fatty acids, as it is usually done to limit beef in the diet. Wang et al (2021) found that the increase in age decreased the contents of C15:0, C18:0, and the sum of SFA and increased the proportions of C14:1 and C16:1. Regarding these fatty acids in our study, only C18:0 showed an increase in its content with increasing slaughter age.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, no significant difference in serum TP, ALB, BUN, UA, and CREA was found among the treatments, indicating that all the amino acids in the diets were enough and balanced; the biochemical indexes in our study were in a similar range compared to a study where a diet containing protected methionine did not affect the metabolic and hematological indicators of beef cattle [ 32 ]. In ruminant animals, the increase in ALT activity has been proved to be associated with liver damage, while the increase in AST activity could indicate a growing intensity of metabolic changes [ 33 ]. In addition, the activity of ALP is related to metabolic syndrome and cardiovascular disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of acetoacetic acid, one of the intermediate metabolites of fatty acid oxidation in the liver ( 30 ), and acetic acid yielded similar results, suggesting that they supplied energy through fatty acid oxidation in the LE group. Owing to a sufficient energy intake in the HE group, the level of fatty acid oxidation in the liver should be lower ( 31 ), and lipid synthesis metabolism should be enhanced ( 32 ). As a result, lipid deposition was higher in the HE group than in the ME group.…”
Section: Discussionmentioning
confidence: 99%